0247 Shift work and incidence of cardiovascular diseases in the danish nurse cohort. (21st August 2017) - Jørgensen, Jeanette Therming; Horn, Rikke; Stayner, Leslie; Hansen, Johnni; Andersen, Zorana Jovanovic
Abstract : Objective: Shift work and risk of cardiovascular diseases (CVD) have been investigated during many decades. The evidence is, however, still conflicting. This study aims to examine whether shift work among Danish female nurses is associated with the risk of CVD. Methods: 28 731 women from the Danish Nurse cohort (>44 years old at recruitment in 1993 or 1999), who reported information on shift work (day, evening, night or rotating), were linked to the Danish National Patient Register, to obtain information on CVD (ICD-10: I00-99; ICD-8: 390–458) hospital contacts (emergency, in- or outpatient) from 1978 until August 2015. We used Cox regression models to examine the association between shift work and the incidence of CVD, defined as the first-ever hospital contact for CVD after cohort baseline, adjusting for the most important risk factors. Results: Of 16 086 nurses without previous CVD events at baseline, 5504 developed CVD during a mean follow-up of 16 years, with an incidence rate of 21.4 cases per 1000 person-years. 63.4% of the nurses reported day work as their primary work schedule, while 10.0%, 5.3% and 21.6% worked in evening, night and rotating shifts, respectively. We found no associations between shift work and the risk of CVD when compared to day workers, with hazard ratio of 0.99 (95% confidence interval 0.91–1.09) for evening, 1.01 (0.90–1.13) for night and 1.03 (0.96–1.10) for rotating shifts, in the fully adjusted model. Conclusion: We found no evidence of an increased risk of CVD among female shift workers.